2002
DOI: 10.1108/01443570210440500
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the sales‐production relationship and customer satisfaction

Abstract: Over the past three decades, many researchers have studied the relationship between sales and production departments. This has raised the question: Does the quality of the relationship between production and sales affect the customer? This study uses survey methodology to examine the link between customer satisfaction and the interface variables (connectedness, conflict, coordination) from both a sales and a production perspective. Customer satisfaction responses are aggregated for each sales-production combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 30 publications
0
39
0
2
Order By: Relevance
“…Even though there appears to be a common acceptance in the literature that the quality of internal processes and internal service is a key influencer of, and contributor to, the quality of external service (see for example (Gremler et al 1994;Parente et al 2002;Zeithaml et al 2008) this paper will argue that public services are currently taking a production or goods-dominant approach to process improvement rather than a service approach. However, it will use this evidence to extend the debate on how Lean can be adapted for a public sector context.…”
mentioning
confidence: 90%
“…Even though there appears to be a common acceptance in the literature that the quality of internal processes and internal service is a key influencer of, and contributor to, the quality of external service (see for example (Gremler et al 1994;Parente et al 2002;Zeithaml et al 2008) this paper will argue that public services are currently taking a production or goods-dominant approach to process improvement rather than a service approach. However, it will use this evidence to extend the debate on how Lean can be adapted for a public sector context.…”
mentioning
confidence: 90%
“…All in all, a rather large number of researchers have suggested that more work is needed in this area (Brooks et al, 1999;Conduit and Mavondo, 2001;Farmer et al, 2001;Kang et al, 2002;Lings, 2000;Parente et al, 2002). This view has provided the basic motivation for this work that will test empirically the following set of hypotheses:…”
Section: Literature Reviewmentioning
confidence: 99%
“…A importância do serviço interno Deming (1986);Feigenbaum (1986);Heskett (1987); Muhlemann et al (1992); Parente et al (2002); Heskett et al (2003) Desenvolvimento de capacidades internas, coordenação e resolução de conflitos Heskett (1986); Parente et al (2002); Laddha et al (2012) Visão estratégica e orientação interna Heskett (1987) Serviço interno e comportamento organizacional George (1990) de determinantes da qualidade e, posteriormente, de dimensões da qualidade, descritas na Tabela 4. Tomando-se como base as 10 dimensões da qualidade mostradas na Tabela 4, foi desenvolvido um questionário denominado de escala (ou instrumento) SERVQUAL, composto por 22 questões as quais utilizavam as diversas ocorrências de satisfação por meio do modelo gap (Parasuraman et al, 1988).…”
Section: Tópico Autoresunclassified